Routine ketorolac at oocyte retrieval decreases postoperative narcotic use by more than 50% - Emily A. Seidler, M.D; Denis A. Vaughan, M.D; Angela Q. Leung, M.D; Denny Sakkas, Ph.D; David A. Ryley, M.D; Alan S. Penzias, M.D (Elsevier, 2021)
Objective: To study the impact of routine ketorolac administration during oocyte retrieval on the proportion of patients who require postoperative narcotics for analgesia. Design: Retrospective cohort study. Setting: Single, university-affiliated infertility clinic. Patient(s): All women undergoing oocyte retrieval between July and November 2016 (non-ketorolac group [NKG]; n = 826) and April-August 2017 (ketorolac group, KG; n = 1780). Intervention(s): A single 30 mg intravenous dose of ketorolac was administered after the oocyte retrieval procedure. Main outcome measure(s): The number of patients who required postoperative narcotic analgesia, postoperative complication rate, and fresh embryo transfer pregnancy outcomes were examined. Result(s): In the KG, we found a significant decrease in the patients who required narcotics after oocyte retrieval compared with the NKG (12% KG vs. 25.5% NKG). We found no significant change in the clinical pregnancy rate (CPR) resulting from fresh embryo transfer after our intervention (NKG CPR 32.6%, KG CPR 32.4%). Furthermore, there was no increase in postoperative bleeding complications in the KG. Conclusion(s): Routine use of ketorolac at the time of oocyte retrieval may decrease the rate of postoperative opioid use without adversely impacting pregnancy and complication rates.